A clinical and in vitro assessment of outpatient parenteral benzylpenicillin and ceftriaxone combination therapy for enterococcal endovascular infections. Issue 3 (7th August 2021) - Ingram, Paul R; Ng, Jacinta; Mathieson, Claire; Mowlaboccus, Shakeel; Coombs, Geoffrey; Raby, Edward; Dyer, John
Abstract: Background: Amoxicillin plus ceftriaxone combination therapy is now standard of care for enterococcal endocarditis. Due to amoxicillin instability in infusion devices, benzylpenicillin plus ceftriaxone may be substituted to facilitate outpatient parenteral antimicrobial therapy (OPAT) delivery, despite lack of guideline endorsement. Objectives: To assess the clinical efficacy of benzylpenicillin plus ceftriaxone for the management of enterococcal endovascular infections, in addition to assessing this combination's in vitro synergy. Patients and methods: Retrospective cohort study assessing unplanned readmissions, relapses and mortality for 20 patients with endovascular Enterococcus faecalis infections treated with benzylpenicillin plus ceftriaxone delivered via OPAT. For a subset of isolates, synergism for both amoxicillin and benzylpenicillin in combination with ceftriaxone was calculated using a chequerboard method. Results: Patients had endovascular infections of native cardiac valves ( n = 11), mechanical or bioprosthetic cardiac valves ( n = 7), pacemaker leads ( n = 1) or left ventricular assistant devices ( n = 1). The median duration of OPAT was 22 days, and the most frequent antimicrobial regimen was benzylpenicillin 14 g/day via continuous infusion and ceftriaxone 4 g once daily via short infusion. Rates of unplanned readmissions were high (30%), although rates of relapsed bacteraemia (5%) and 1 year mortality (15%) were comparable to the published literature. Benzylpenicillin less frequently displayed a synergistic interaction with ceftriaxone when compared with amoxicillin (3 versus 4 out of 6 isolates). Conclusions: Lower rates of synergistic antimicrobial interaction and a significant proportion of unplanned readmissions suggest clinicians should exercise caution when treating enterococcal endovascular infection utilizing a combination of benzylpenicillin and ceftriaxone via OPAT.